Numerical Modeling of Lawsonite Thin Film as Radiative Cooling Minerals for Harvesting Dew (Global Journal of Science Frontier Research, 2022)
Abstract not found
Keywords: condensation; radiative cooling; lawsonite; harvesting dew; dew yield